Nutrient and heavy metal storage and mobility within sediments in Kouris Reservoir, Cyprus. Issue 1 (March 2017) - Tzoraki, O.; Dörflinger, G.; Demetriou, C.
Abstract: The objective of this study was to evaluate the risks associated with nutrient and heavy metal pollution in the water and sediments of Kouris Reservoir in Cyprus, and to recommend applicable measures to alleviate them. The reservoir drainage area contains various historic abandoned copper mines existing in an ophiolite geological substrate. Kouris Reservoir water is classified as oligotrophic to mesotrophic, with phosphorus being the limiting factor for algae growth. The thermal stratification of the reservoir enhances anoxic conditions in the reservoir hypolimnion, initiating phosphorus release back into the water column from the lake bottom sediments. The increased phosphorus release, in combination with increased water temperatures during the summer months (i.e. reaching 27 °C in August), may be the key factors enhancing the growth of microbial communities and cyanobacteria blooms. The sediment of Kouris Reservoir is classified as 'low risk' on the basis of the Ecological Risk Index scheme, in contrast to the Geoaccumulation Index, which indicates a moderate degree of contamination for chromium (Cr), nickel (Ni) and copper (Cu), and a high degree for lead (Pb). Heavy metals are strongly bound to the sediment matrix at pH values between 7 and 9, but can be released back into the water column at potential acid pH values. In addition, the sediments exhibit a high copper and chromium absorption affinity under current water quality conditions in the reservoir, as shown by batch absorption experiments. The experimental results suggest dredging of the reservoir sediment, and its subsequent dumping of the sediments near influent streams, would have adverse effects on the environment in the event of acid rain or other environmental changes that might acidify the sediment.